Intercultural Learning Supported by Technology: A Small-Scale Systematic Review - Wayan Sintawati (International Journal of Education and Learning, 2019)
Intercultural interaction and communication are rapidly increasing throughout the world. In a fast-growing and globalised world, the ability to communicate with people across cultures is important. This study discusses describing the Byram model of the environment used in learning, culture, language, and problems and solutions for the future and using qualitative methods by following the pattern of previous research with the primary sources from Google Scholar, Baidu Scholar, Science Direct and Mendeley's search platform. The result from this research is (1) This ICC model can be used as a useful reference and guideline for teacher planning in discussions and discussions to develop IC students. (2) Inter-cultural learning is more effective and more impressive such as Holograms, VR technology, Artificial Intelligence, cloud, etc. (3) The most widely used topics in the studio are culture (n = 4), daily life (n = 2), controversial issues, language, communication, physical space (time resolution), resolution, resolution, and stereotyping. (4) Problems, solutions, and suggestions for future studies and practices. Most of the problems that most of us find here are socialisation. The solution to this problem is to familiarise students with this communication tool.